Synthesis of Some Schiff's Bases Containing 1,3,4-Thiadiazole Ring and Their Properties as Antioxidants - Al-Shammary, Kahlan M Abbas (Al-Nahrain Journal of Science, 2012)
A series of Schiff's bases containing 1,3,4-thiadiazole (2,5-di(N-substitutedbenzylideneamino)-1,3,4-thiadiazole) were prepared through the reaction of thiosemicarbazide with chloro cyanide.The product was directly reacted with benzaldehyde and substituted benzaldehydes. The syntheticcompounds (0-10) were identified using the analytical and spectral means. The antioxidantproperties were measured of the prepared compounds using the metal ions (Fe+3, Cu+2), andFerrozine and 2,9-dimethyl-1,10-phenanthroline (neocuproine). The results showed that thecompound no. 5 [2,5-di(N-(4-hydroxybenzylideneamino)-1,3,4-thiadiazole] reveals the highestantioxidant activity through this work.